Meet RODA, a full-fledged digital repository for long-term preservation - Castro, Rui (2011)
RODA is an open-source full-fledged digital preservation repository capable of ingesting, managing and providing continuous access to various types of digital objects, namely text-documents, raster images, relational databases, video and audio. It is supported by open-source technologies and makes use of existing standards such as the OAIS, METS, EAD and PREMIS.